Impressions of voice interaction in digital games: a comparative study between humans and generative artificial intelligence - Carvalho, Vítor Marques (2023)
This Master’s dissertation provides a comprehensive and complex synthesis of the field of voice interaction in digital games, addressing its relevance in both academic and industrial contexts to produce more immersive and engaging experiences. The study highlights the challenges faced by this mode of interaction over the years and the technological evolution that followed several attempts to establish a profitable product in the gaming market. The research presents evidence of the perception of a highly specialized audience on the different modalities of voice interaction in digital games, seeking to draw a comparative parallel between the state of the art and current reality. These findings can provide tangible benefits to improve gameplay experiences and reduce disruptive behaviors in academia and the gaming market. Additionally, this work also highlights the influence and particularities of different scenarios of voice interaction on the engagement and experience of human participants in this study, as well as their motivations and limitations regarding current technology. Furthermore, it presents a comparative study of the impressions and perspectives on voice interaction in digital games deriving from different AIs (ChatGPT, Bing Chat, and Google Bard). In this way, the opinions of the AIs and human participants were successfully contrasted, providing a more comprehensive understanding of the possible advantages and challenges of voice interaction in this context, additionally, projecting future evolution scenarios that extend beyond entertainment, for example, into domains such as health. Based on this comprehensive comparative study, opportunities for improving voice interaction in digital games were identified that anticipate future trends in this area. Keywords: Voice Interaction. Digital Games. Human Participants. Generative Artificial Intelligence